Novel SAR for quinazoline inhibitors of EHMT1 and EHMT2. Issue 17 (1st September 2019) - Leenders, Ruben; Zijlmans, Remco; van Bree, Bart; van de Sande, Marc; Trivarelli, Federica; Damen, Eddy; Wegert, Anita; Müller, Daniel; Ehlert, Jan Erik; Feger, Daniel; Heidemann-Dinger, Carolin; Kubbutat, Michael; et al.
Graphical abstract: Abstract: Detailed structure activity relationship of two series of quinazoline EHMT1/EHMT2 inhibitors (UNC0224 andUNC0638 ) have been elaborated. New and active alternatives are presented for the ubiquitous substitution patterns found in literature for the linker to the lysine mimicking region and the lysine mimic itself. These findings could allow for advancing EHMT1/EHMT2 inhibitors of that type beyond tool compounds by fine-tuning physicochemical properties making these inhibitors more drug-like. .